1998
DOI: 10.1093/oxfordjournals.molbev.a026022
|View full text |Cite
|
Sign up to set email alerts
|

Ancient large-scale genome duplications: phylogenetic and linkage analyses shed light on chordate genome evolution

Abstract: Paralogous genes from several families were found in four human chromosome regions (4p16, 5q33-35, 8p12-21, and 10q24-26), suggesting that their common ancestral region underwent several rounds of large-scale duplication. Searches in the EMBL databases, followed by phylogenetic analyses, showed that cognates (orthologs) of human duplicated genes can be found in other vertebrates, including bony fishes. In contrast, within each family, only one gene showing the same high degree of similarity with all the duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(85 citation statements)
references
References 56 publications
4
80
0
1
Order By: Relevance
“…Evidence in favor of the 1-2-4 hypothesis is the observation that genes from the same gene family are often arranged in linked clusters that maintain the same gene order on different chromosomes (e.g. see [8]). This synteny of gene clusters (the location of two genes within a linkage group but on different chromosomes) is often retained across large evolutionary distances, such as between fish, mice and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence in favor of the 1-2-4 hypothesis is the observation that genes from the same gene family are often arranged in linked clusters that maintain the same gene order on different chromosomes (e.g. see [8]). This synteny of gene clusters (the location of two genes within a linkage group but on different chromosomes) is often retained across large evolutionary distances, such as between fish, mice and humans.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of three 'large' quadrupled regions in the unfinished human genome, namely the major histocompatibility complex (MHC; human chromosome (Hsa) l, 6, 9 and 19), an extended Hox (Hsa 2, 7, 12 and 17) and the fibroblast growth factor receptor (FGFR; Hsa 4, 5, 8 and l0) regions, which included genes duplicated w530-738 Mya strongly supported tetraploidy [5][6][7][8][9]. These rounds of duplication could have happened in short succession within 90-106 Mya [10].…”
Section: Introductionmentioning
confidence: 99%
“…First, we confirmed that our non-binary algorithms perform identically to Least Common Ancestor reconciliation when applied to binary trees. We tested the new algorithms in NOTUNG on a benchmark of 15 wellstudied, binary trees 5,17,32,38 and verified that the results were the same as those generated by the binary version of NOTUNG, as well as those of the original authors. Second, we considered performance.…”
Section: Resultsmentioning
confidence: 78%